2021
DOI: 10.3390/ijms22168501
|View full text |Cite
|
Sign up to set email alerts
|

Different Patterns of mRNA Nuclear Retention during Meiotic Prophase in Larch Microsporocytes

Abstract: Recent studies show a crucial role of post-transcriptional processes in the regulation of gene expression. Our research has shown that mRNA retention in the nucleus plays a significant role in such regulation. We studied larch microsporocytes during meiotic prophase, characterized by pulsatile transcriptional activity. After each pulse, the transcriptional activity is silenced, but the transcripts synthesized at this time are not exported immediately to the cytoplasm but are retained in the cell nucleus and es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Accordingly, several reports have demonstrated that mRNA nuclear retention due to retained introns can also be used as a mechanism for the temporal control of gene expression. Certain introns were found to be post-transcriptionally removed at distinct times, allowing regulated mRNA export and translation, which is especially relevant during cell differentiation [23][24][25].…”
Section: Quality Control Of Splicing In the Nucleus-retention Or Export Of Mrnamentioning
confidence: 99%
“…Accordingly, several reports have demonstrated that mRNA nuclear retention due to retained introns can also be used as a mechanism for the temporal control of gene expression. Certain introns were found to be post-transcriptionally removed at distinct times, allowing regulated mRNA export and translation, which is especially relevant during cell differentiation [23][24][25].…”
Section: Quality Control Of Splicing In the Nucleus-retention Or Export Of Mrnamentioning
confidence: 99%